2021
DOI: 10.1002/cpt.2459
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Modeling and Simulation Framework to Support Candidate and Dose Selection of Anti‐SARS‐CoV‐2 Monoclonal Antibodies to Advance Bamlanivimab Into a First‐in‐Human Clinical Trial

Abstract: Neutralizing monoclonal antibodies (mAb), novel therapeutics for the treatment of coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2), have been urgently researched from the start of the pandemic. The selection of the optimal mAb candidate and therapeutic dose were expedited using open‐access in silico models. The maximally effective therapeutic mAb dose was determined through two approaches; both expanded on innovative, open‐science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…The phase 2 single-dose level of BEB (175 mg) was selected using PK/PD modeling which leveraged results from multiple BAM+ETE studies. The PK/PD modeling approach was deemed reliable because the approach had been previously implemented to predict the efficacious doses of BAM+ETE, before any clinical trial data was available 17 Overall, the safety data was consistent with other clinical trials investigating neutralizing mAbs to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The phase 2 single-dose level of BEB (175 mg) was selected using PK/PD modeling which leveraged results from multiple BAM+ETE studies. The PK/PD modeling approach was deemed reliable because the approach had been previously implemented to predict the efficacious doses of BAM+ETE, before any clinical trial data was available 17 Overall, the safety data was consistent with other clinical trials investigating neutralizing mAbs to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 54%
“…The phase 2 single-dose level of BEB (175 mg) was selected using PK/PD modeling which leveraged results from multiple BAM+ETE studies. The PK/PD modeling approach was deemed reliable because the approach had been previously implemented to predict the efficacious doses of BAM+ETE, before any clinical trial data was available 17 . The clinical trial data later confirmed the model predictions of 700 mg BAM and 1400 mg ETE resulting in maximum drug effect; the PK/PD modeling approach described in Chigutsa et al, 2022 17 was further strengthened and refined through incorporating the BAM+ETE clinical trial data to update the model 24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations